2014
DOI: 10.1097/mnh.0000000000000061
|View full text |Cite
|
Sign up to set email alerts
|

Novel risk factors for acute kidney injury

Abstract: Novel risk factors for AKI have been identified but more work is necessary to investigate the nature of the association. There is no evidence that correction of hyperuricaemia or hypoalbuminaemia is beneficial but high-risk exposures should be avoided in patients at risk of AKI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 66 publications
1
15
1
1
Order By: Relevance
“…Obesity is generally accepted as a risk factor for the development of AKI;60 however, one study found that increased BMI is associated with decreased mortality from AKI in elderly surgical patients 61. The inverse relationship of obesity to AKI in our results is puzzling, though potentially explained by the fact that the addition of occupational characteristics attenuated the relationship of BMI to AKI.…”
Section: Discussioncontrasting
confidence: 66%
“…Obesity is generally accepted as a risk factor for the development of AKI;60 however, one study found that increased BMI is associated with decreased mortality from AKI in elderly surgical patients 61. The inverse relationship of obesity to AKI in our results is puzzling, though potentially explained by the fact that the addition of occupational characteristics attenuated the relationship of BMI to AKI.…”
Section: Discussioncontrasting
confidence: 66%
“…In recent years, there have been several reports regarding novel and previously unknown risk factors for AKI, such as hyperuricemia 19 , hypoalbuminemia 20 , obesity 21 , obstructive sleep apnea 22 , hypochloremia and hyperchloremia 23 . In our study, BMI and obesity (COM2) were both selected in the top ten by several FS methods as shown in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies have consistently reported that the risk factors associated with a poor AKI prognosis include advancing age, cardiovascular disease, AKI stage, and so on [21]. In addition to examining these basic risk factors, we also systemically and comprehensively collected the laboratory indicators of patients with AKI, and examined the APACHE II and SOFA scores of these patients to better predict the mortality risk of AKI patients.…”
Section: Discussionmentioning
confidence: 99%
“…High SUA concentrations are significantly correlated with a decline in residual kidney function after adjusting for confounding factors [36]. Uric acid could have pro-inflammatory effects, increase oxidative stress, and damage the microcirculation [21], thereby increasing mortality risk and explaining why a high SUA level can serve as a marker of poor prognosis. Nevertheless, as high SUA might be a symptom of AKI, it is unclear whether the poor prognosis is due to uric acid itself or to AKI.…”
Section: Discussionmentioning
confidence: 99%